Identification of microbial communities, with a focus on foodborne pathogens, during kimchi manufacturing process using culture-independent and -dependent analyses. (August 2017) - Lee, Hae-Won; Yoon, So-Ra; Kim, Su-Ji; Lee, Hee Min; Lee, Jae Yong; Lee, Ji-Hyun; Kim, Sung Hyun; Ha, Ji-Hyoung
Abstract: Little is known about microbial communities associated with the kimchi manufacturing process. We investigated the structure of microbial communities, focusing on foodborne pathogens, such as Bacillus cereus, enterohemorrhagic Escherichia coli, Clostridium perfringens, Campylobacter jejuni, Staphylococcus aureus, Salmonella spp., Listeria monocytogenes, and Yersinia enterocolitica, during the kimchi manufacturing process, including the brining, washing, and condiment stuffing phases, using culture-dependent and culture-independent analyses. Foodborne pathogens were not identified in any test sample by the culture-dependent analysis, whereas the culture-independent analysis targeting the hypervariable regions V3 and V4 of the 16S rRNA gene detected traces of general or potential foodborne pathogens, such as Campylobacter spp., Enterobacter spp., Escherichia or Shigella spp., Serratia spp., Vibrio spp., Aeromonas spp., Acinetobacter spp., Pseudomonas spp., and Enterococcus spp. However, as the kimchi manufacturing process proceeded, the structure of the microbial community changed, and potential foodborne pathogens were replaced by probiotics, such as lactic acid bacteria. Our results suggest that it may be worth utilizing the culture-independent analysis to complement the culture-dependent analysis for microbiological quality control of the kimchi manufacturing process. Highlights: We characterized the microbial diversity during the kimchi manufacturing process. Numbers of potential pathogens were decreased by washing and proliferation of LABs. Both culture-dependent and -independent microbiological quality control is important.